A YouTube analysis of Muslim scholar reactions to Trump’s electoral outcome: social work implications - Yusof, Yusmarhaini; Syed-Ahmad, Sharifah Fatimah; Mainal, Azizah; Murphy, Jamie (Taylor & Francis, 2020)
This paper investigated Muslim scholars’ immediate YouTube reactions towards President Trump during the November 2016 post-election week. Muslim scholars, also known as Imams or religious leaders, can promote social justice and rally the Muslim community, positively or negatively. Thematic analysis suggested reasons for Trump winning the election, and issues of unity and social justice. The analysis implies that Muslim scholars can be positive first responders and help bind both their Muslim and neighborhood community. The results of this study can help social workers together with Muslim scholars devise better interventions and use online media for community outreach. © 2019, © 2019 Taylor & Francis.